Correlation of Electronic (Web-Based and Smartphone) Administration of Measures of Pelvic Floor Dysfunction: A Randomized Controlled Trial. Issue 6 (June 2020) - Grimes, Cara L.; Antosh, Danielle D.; Oliphant, Sallie; Yurteri-Kaplan, Ladin; Kim-Fine, Shunaha; Melamud, Gabriel; Heisler, Christine; Chung, Doreen E.
Abstract : Objective: We hypothesized that instruments of pelvic floor dysfunction would yield similar responses on web-based and smartphone administration compared with paper. Methods: Subjects presenting with pelvic floor disorders were prospectively enrolled at 5 sites and invited to complete 4 validated pelvic floor disorder questionnaires (Pelvic Floor Distress Inventory 20, Pelvic Floor Impact Questionnaire 7, Pelvic Organ Prolapse/Urinary Incontinence Sexual Function Questionnaire 12, Bristol Stool Scale) on both paper and electronic formats, 2 weeks apart, with the order of administration being randomized. Participants completed the questionnaires electronically on the internet via REDCap or using the PelvicTrack App on a smartphone or tablet. Results: Two hundred thirty-four subjects were enrolled, and 132 subjects (56%) completed both sets of questionnaires with no intervening treatment. This group was 58 (±15) years old with body mass index 28 (±6) kg/m 2 and parity 2 (1, 3) and was 77% white, 6% African American, 7% Asian, and 10% other. Presenting complaints were classified as 58% urinary, 37% prolapse, and 5% defecatory. There was no difference in overall demographic information between those who completed the second round of questionnaires and those who did not. There was no difference in age between those who chose to complete the questionnaires via REDcap and those who chose to complete the questionnaires via smartphone. Correlation coefficients between questionnaire administration range from 0.5 to 0.8. There was no significant difference in the responses for each total scale and individual scale between the first or second administration. Conclusions: We demonstrated moderate to strong reliability between scales of pelvic floor dysfunction administered electronically compared with paper version. Our results strongly suggest that it is feasible and reliable to administer pelvic floor questionnaires in an electronic format on REDCap and on smartphones. Abstract : Supplemental digital content is available in the text.